Diagnostic systémique de l’adaptabilité du territoire camarguais face à la montée du niveau de la mer - Sophie Liziard; Christine Voiron-Canicio (Bulletin de l’Association de Géographes Français)
Conducted by the ESPACE French laboratory with the Ressource research consultancy and the Tour du Valat, the CAMPLAN research program on the integrated management of the Camargue and Plan-du-Bourg hydro-system, is based on the observation made by several managers of natural areas of this territory: an increasing inability of the water governance to maintain the adaptive capacity of the hydraulic system faced with global change, and most particularly with sea level rise. In this research program, our goal was to combine the knowledge produced by the multidisciplinary research team in order to identify the elements which, in the functioning of the territorial system, are favourable and unfavourable to its adaptation. The complexity and the breadth of the gathered knowledge have required a systemic approach. The analysis of the structure of the constitutive relationships of the Camargue system brought to light two ways to adapt, from which the levers and brakes to the adaptability of the Camargue area were examined.